Analisis Penentuan Sektor Unggulan di Kabupaten Sumedang Provinsi Jawa Barat - Alam Masruri, Fahrul; Cahyono; Nugrahana Fitria Ruhyana (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
The purpose of this study was to analyze the potential leading sectors to be developed in Sumedang Regency. During the last 10 years, Sumedang's economy has been dominated by 3 main sectors. Of the three sectors and 14 other sectors, it is not yet known which one is the most superior and has the potential to be the main driving force of Sumedang's economy. This research method uses a sequential explanatory method, starting with LQ approach, Shift Share and overlay, then the results are followed by a qualitative approach by conducting a Focus Group Discussion with economic development stakeholders in Sumedang Regency. There are 11 sectors that are categorized as basic sectors, but there are only 2 sectors that are able to grow faster and have competitiveness compared to the same sector in West Java, namely the construction sector and the financial services sector and insurance. The agriculture, forestry and fisheries sectors are considered to have the potential to be the main driver of the Sumedang economy because it is a basic sector, has competitiveness, being a resistant sector during the Covid-19 pandemic, as a support for food security, a natural social safety net, and strengthening rural economic activity.